2022
DOI: 10.24239/jimpe.v1i2.1216
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Sumber Daya Manusia pada UPT Perpustakaan Universitas Tadulako Palu

Abstract: Penelitian ini dilakukan untuk mengatasi kesenjangan prestasi kerja pegawai administrasi IAIN Palu. Tujuan dilakukan penelitian ini adalah untuk mengetahui kondisi budaya organisasi pegawai administrasi di IAIN Palu serta meningkatkananalisis budaya organisasi dalam meningkatkan prestasi kerja pegawai administrasi di IAIN Palu. Penelitian ini menggunakan jenis peneletian kualitatif. Sumber data diperoleh dari data primer (secara langsung) adalah hasil dari fiel research (penelitian lapangan) yaitu wawancara de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…In the next iteration, axial coding was carried out by connecting the emerging categories and themes (Corbin and Strauss, 1990). At this stage, various types of open coding are then extracted into a smaller number based on the core themes conveyed by the informants (Supiani, Nurdin, Syahid, & Fakhrurrozi, 2022). In the third iteration stage, selective coding assists the researcher in an in-depth study of the various categories that have been identified in the second coding stage by "refining their meaning and articulating the relationships between the various categories and themes" (Jin & Robey, 2008, p. 183) to enable giving birth to new theories and solutions to problems that arise in interviews.…”
Section: Methodsmentioning
confidence: 99%
“…In the next iteration, axial coding was carried out by connecting the emerging categories and themes (Corbin and Strauss, 1990). At this stage, various types of open coding are then extracted into a smaller number based on the core themes conveyed by the informants (Supiani, Nurdin, Syahid, & Fakhrurrozi, 2022). In the third iteration stage, selective coding assists the researcher in an in-depth study of the various categories that have been identified in the second coding stage by "refining their meaning and articulating the relationships between the various categories and themes" (Jin & Robey, 2008, p. 183) to enable giving birth to new theories and solutions to problems that arise in interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The research uses a qualitative method approach (Creswell, 1998;G. Morgan & Smircich, 1980).The qualitative research method is a research method that focuses on studying phenomena in depth on a research topic (Supiani, Nurdin, Syahid, & Fakhrurrozi, 2022).This in-depth study was obtained through interaction with sources or informants (Haryanto, Nurdin, & Ubadah, 2022). In this research, the sources are millennial preachers who are used to preaching via the Internet.The resource persons came from young Ulama, who are members of the Indonesian Ulema Council, and also young da'i, who come from other religious organizations.…”
Section: Methodsmentioning
confidence: 99%
“…Kedudukan manajemen pendidikan dalam memberikan dukungan penyelenggaraan pendidikan sangat strategis, karena dengan keberadaan manajemen pendidikan usaha pendidikan berjalan dengan baik, bahkan manajemen pendidikan merupakan suatu kegiatan atau rangkaian kegiatan yang berupa proses pengelolaan usaha kerja sama sekelompok manusia yang tergabung dalam organisasi pendidikan, untuk mencapai tujuan pendidikan yang telah diterapkan sebelumnya, agar efektif dan efesien (Supiani, Nurdin, Syahid, & Fakhrurrozi, 2022).…”
Section: Implementasi Manajemen Pendidikanunclassified